Economic analysis of tambaqui (Colossoma macropomum) cultivation in the region of ariquemes-ro, brazil - Meante, Raica Esteves Xavier [UNESP]; de Sá, Marco Eustáquio [UNESP]; Costa, Silvia Maria Almeida Lima [UNESP] (My University, 2021)
The scope of this article was to carry out the economic analysis of three fish farming projects, endowed with different technological standards with the description of the production process of tambaqui (Colossoma macropomum), a native species in the Amazon. The research was carried out in the municipality of Ariquemes, considered the largest captive fish production hub in the state of Rondônia. To carry out this research, the technique of data collection of indirect documentation and interviews with fish producers was used, using a semi-structured questionnaire, in addition to visits to the enterprises. The economic viability was configured for the three fish farms, here called X, Y and Z with profitability indexes of 27.25%, 29.75% and 25%, respectively. The IRR ranged from 12.98% to 14.98% and the simple payback ranged from 5.46 to 6.84 years. The Y fish farm, which holds the most advanced technologies, achieved the highest productivity per area and showed better economic indices, proving a positive response to efforts to improve the technological packages adopted. The sensitivity analysis considered seven different scenarios and the projects proved to be viable up to a 10% increase in production costs with normal revenues.
Keywords: Fish farming; Production costs; Tambaqui